Sheehan's syndrome: A clinical, biochemical, hormonal, radiological, bone mineral density and quality of life assessment - Manish Gutch; Sukriti Kumar; Sanjay Saran; Keshav Kumar Gupta; Syed Mohd Razi; Jaideep Tomar; Kamlendra Verma (Wolters Kluwer Medknow Publications, 2014)
Background: Sheehan's syndrome (SS) or postpartum pituitary necrosis though rare, still remains one of the commonest causes of hypopituitarism in the Indian subcontinent. The clinical presentation is often variable with abrupt or insidiously onset pituitary insufficiency after heavy intrapartum or postpartum hemorrhage. Aims: To study the demographic profile, hormonal profile, as well as the quality of life of patients of SS, and the effect of hormonal replacement therapy on outcome. Materials and Methods: All patients previously diagnosed with Sheehan's syndrome or newly admitted during the study period of 2011-2013 were enrolled in the study after obtaining informed consent. Their clinical, biochemical, hormonal, radiological and bone mineral density (BMD) data were collected. The quality of life (QoL) was assessed using the disease-specific questionnaire both before and after hormone replacement therapy. Result: Twenty three patients were enrolled in the study, the mean age of diagnosis was 43.4 ± 14.2 years; mean diagnostic delay was 13.2 ± 7.4 years. Secondary amenorrhea and lactation failure were the most common clinical presentations. The mean total tetraiodothyronine (T4), peak stimulated cortisol, stimulated growth hormone (GH), and prolactin (PRL) levels were low. The gonadotropins [follicle stimulating hormone (FSH) and luteinizing hormone (LH)] were inappropriately normal in the presence of amenorrhea. Anemia was the most common hematological abnormality seen in 69.5% of patients, while 39.1% of patients had hyponatermia. BMD assessment (n = 23) was suggestive of low bone mass. The QoL improved significantly (P < 0.05) in patients after one year of hormonal replacement therapy. Conclusion: Sheehan's syndrome resulted in multiple pituitary hormone deficiencies in all patients. Anemia, hyponatremia, and low bone mass were frequently seen in patients with Sheehan's syndrome. The QoL improved significantly (P < 0.05) after hormonal replacement therapy.